Teachers, digital technologies and scholar inclusion: challenges of special educational policy at a brazilian region - Ferreira, Fabiane da Silva (2021)
The purpose of this article is to know the teachers' conceptions about the use of digital technologies in pedagogical activities, in a context of diversity in a region of Brazil that implemented the national policy of inclusive education. The methodological procedures consisted of consulting documents and conducting semi-structured interviews with teachers who work in regular classes and specialized educational classes, with children in the literacy stage. The school is distinguished for receiving a large number of special education students, due it includes a specialized support center, and students whose Spanish is their mother language, because it is located close to the border between Brazil and Bolivia.